Cognitive Remediation Interventions in Autism Spectrum Condition: A Systematic Review - Dandil, Yasemin; Smith, Katherine; Kinnaird, Emma; Toloza, Cindy; Tchanturia, Kate (Frontiers in Psychiatry, 2020)
Background: Autism spectrum condition (ASC) is a lifelong neurodevelopmental condition characterised by difficulties in social cognition and heterogeneity of executive function which are suggested to be underpinned by neurobiological, prenatal and genetic factors. Cognitive remediation (CR) interventions are frequently used to address cognitive characteristics and improve cognitive and general functioning. However, the evidence is limited for ASC. This systematic review is the first to provide a narrative synthesis of all studies of CR interventions and ASC. The review aimed to delineate the development of research in this area in both adolescents and adults, with implications for clinical practice and future research. Method: The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐analysis (PRISMA) statement. The literature was reviewed using the PubMed, PsycINFO, Web of Science, Scopus and Embase from inception to 1st April 2020. Out of 1,503 publications, a total of 13 papers were identified as being relevant for the review. Results: The 13 studies meeting the inclusion criteria were: four randomised control trials (RCTs); two non-randomised control trials, four case series, two feasibility studies and one case study. A narrative synthesis of the data suggested that CR interventions are potentially effective in improving social cognition and cognitive functioning in ASC. RCTs supported the efficacy of CR interventions in improving social cognition and executive functioning. Non-randomised control trials provided evidence for the effectiveness of social cognition remediation interventions in ASC. Case series and a case study have also supported the feasibility of CR interventions, including reflections on their adaptation for ASC populations and the positive feedback from participants. Conclusions: CR interventions are potentially effective in improving social cognition and cognitive functioning in ASC. However, the generalisability of the included empirical studies was hampered by several methodological limitations. To further strengthen understandings of the effectiveness of CR interventions for ASC, future RCTs are needed with larger sample sizes in exploring the long-term effectiveness of CR interventions, using age-appropriate valid and reliable outcome measures. They should also consider the heterogeneity in neuropsychological functioning in ASC and the mediating and moderating mechanisms of the CR intervention for ASC.